2020
DOI: 10.1186/s13020-020-00316-y
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic effect and action mechanism of Salvia miltiorrhiza and Panax notoginseng herbal pair on the zebrafish

Abstract: Background: Salvia miltiorrhiza (Danshen, DS) and Panax notoginseng (Sanqi, SQ) are famous traditional Chinese herbs, and their herbal pair (DS-SQ) has been popular used as anti-thrombotic medicines. However, there is still a lack of sufficient scientific evidence to illustrate the optimum combination ratio of these two herbs as well as its action mechanisms. The purpose of this study is to investigate the anti-thrombotic effects of DS-SQ on zebrafish and explore its possible action mechanism. Methods: Firstly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Therefore, they can be used to construct many pathological models. For example, sleep deprivation model was induced by light stimulation [ 49 ], depression model was induced by reserpine [ 50 ], thrombus model was induced by phenylhydrazine (PHZ) [ 51 ], epilepsy model was induced by pentylenetetrazol (PTZ) [ 52 ], vascular insufficiency model was induced by tyrosine kinase inhibitor [ 53 ], vascular defect model was induced by axitinib [ 54 ], and sapje strain model was always used for muscle atrophy [ 55 ]. GCs are only recognized to induce osteoporosis and cannot be used to induce other diseases in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they can be used to construct many pathological models. For example, sleep deprivation model was induced by light stimulation [ 49 ], depression model was induced by reserpine [ 50 ], thrombus model was induced by phenylhydrazine (PHZ) [ 51 ], epilepsy model was induced by pentylenetetrazol (PTZ) [ 52 ], vascular insufficiency model was induced by tyrosine kinase inhibitor [ 53 ], vascular defect model was induced by axitinib [ 54 ], and sapje strain model was always used for muscle atrophy [ 55 ]. GCs are only recognized to induce osteoporosis and cannot be used to induce other diseases in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Salvia miltiorrhiza , Angelica sinensis , and Ligusticum chuanxiong improve blood circulation [ 30 32 ]. In addition, Salvia miltiorrhiza and Radix Angelicae sinensis prevent thrombosis [ 33 , 34 ], whereas Salvia miltiorrhiza and Codonopsispilosula improve the microcirculation [ 30 , 35 , 36 ] and regulate immunity [ 37 39 ]. In addition, the tonic recipe also intervenes in the metabolic pathways of the interconversion of pentose and glucuronide, lysine degradation, and histidine metabolism in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Their results confirmed that rosmarinic acid, shikimic acid, and salvianolic acid B present in these extracts showed good antiplatelet aggregation effects. This mechanism of inhibiting platelet aggregation involves the downregulation of PKC and vWF expression [ 51 ]. Overall, the antiplatelet aggregation effect of PBCRBSCM is definite, and its mechanism mainly involves inhibiting the levels of Ca2+/increasing the levels of cAMP, inhibiting the activation of integrin- α IIb/ β 3, and downregulating the expressions of FIB and vWF.…”
Section: The Mechanisms Underlying the Antiplatelet Effect Of Pbcrbscmmentioning
confidence: 99%